2015
DOI: 10.1021/acs.macromol.5b01289
|View full text |Cite
|
Sign up to set email alerts
|

Instability of Surface-Grafted Weak Polyacid Brushes on Flat Substrates

Abstract: We study the stability of weak polyacid brush (WPAB) gradients in aqueous media covering a range in grafting density (σ) spanning 0.05−0.5 chains/nm 2 using two analogous surface-anchored bromoisobutyrate-based initiators for atom transfer radical polymerization (ATRP) bearing either an ester or amide linker. Variations in dry thickness of ester-based WPABs as a function of time and pH are consistent with WPAB degrafting via linker hydrolysis catalyzed by mechanical tension in the grafted chains. Sources of te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
47
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 43 publications
(120 reference statements)
4
47
1
Order By: Relevance
“…The results suggest that as the degree of charging in the brush increases, the stability of the layer is decreased. Similar to our finding, Galvin et al 31 observed an increasing degradation rate depending on the degree of charging. They immersed weak polyacid brushes in buffer solutions with different pHs.…”
Section: Synthesis Of Pebssupporting
confidence: 93%
See 3 more Smart Citations
“…The results suggest that as the degree of charging in the brush increases, the stability of the layer is decreased. Similar to our finding, Galvin et al 31 observed an increasing degradation rate depending on the degree of charging. They immersed weak polyacid brushes in buffer solutions with different pHs.…”
Section: Synthesis Of Pebssupporting
confidence: 93%
“…This explanation is also in agreement with the literature in so far that the presence of nucleophiles enhances the degrafting process of polymer brushes. 31,41,63 It was reported that a tethered macromolecule experiences the largest tension in the surface linker that binds the polymer chain to the rigid surface 45,46 which enhances the degrafting. 30 Since the tension on the polymer brushes is directly related to the grafting density, a series of PMeVP brushes with graft densities ranging from 0.0069 to 0.1693 μmol m −2 were exposed to water at 22 C for different periods of time to determine the effect of grafting density on the stability of strong PEBs.…”
Section: Synthesis Of Pebsmentioning
confidence: 99%
See 2 more Smart Citations
“…We can make a few conclusions from the experimental results discussed previously and from earlier publications. 40,44,45,[65][66][67] From the data in Figure 1, degrafting involves base-catalyzed hydrolysis that takes place in the initiator centers. The BMPUS initiators have two kinds of bonds that can be hydrolyzed: 1) ester/amide bond close to the initiating center, and 2) siloxane bond.…”
Section: Resultsmentioning
confidence: 99%